2014
DOI: 10.1002/2013ja019178
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind control of auroral Alfvénic power generated in the magnetotail

Abstract: The effects of solar wind driving conditions on the polar distribution of large‐scale, nondispersive Alfvénic Poynting flux at low altitude during steady magnetosphere convections are studied using three‐dimensional global simulations of the solar wind‐magnetosphere‐ionosphere interaction. Results from 18 test simulations driven by steady upstream solar wind (SW) and interplanetary magnetic field (IMF) conditions are used to investigate the relationship between SW/IMF driving and low‐altitude signatures of lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 53 publications
4
35
0
Order By: Relevance
“…The simulated hemispheric broadband power increases similarly with d Φ MP /d t but with relatively large scatter. The large scatter in the simulated broadband power may be related to a significant IMF B y in the driving condition [ Zhang et al , ]. Overall, the linear fit of the scattered data points is approximately consistent with the OVATION Prime model as suggested also by the ideal test simulations discussed in section 4.1.…”
Section: Model Comparisonssupporting
confidence: 69%
“…The simulated hemispheric broadband power increases similarly with d Φ MP /d t but with relatively large scatter. The large scatter in the simulated broadband power may be related to a significant IMF B y in the driving condition [ Zhang et al , ]. Overall, the linear fit of the scattered data points is approximately consistent with the OVATION Prime model as suggested also by the ideal test simulations discussed in section 4.1.…”
Section: Model Comparisonssupporting
confidence: 69%
“…Chaston et al [2007] and Zhang et al [2014] showed that Alfvénic Poynting flux convergence in the premidnight regime is several times more energetic than on the dayside and that this pattern also appears in the energetic electron fluxes. Chaston et al [2007] and Zhang et al [2014] showed that Alfvénic Poynting flux convergence in the premidnight regime is several times more energetic than on the dayside and that this pattern also appears in the energetic electron fluxes.…”
Section: Relationship Between Eof3 and Alfvén Poynting Fluxmentioning
confidence: 98%
“…We take the next step in 3-D exploration of the ionosphere by presenting the first objective characterization of the primary modes of variability of E region, height-dependent conductivities over the entire polar region using spectrally resolved in situ particle measurements from the Special Sensor J (SSJ) instrument on board the F6-F8 and F16-F18 Defense Meteorological Satellite Program (DMSP) satellites. The third mode seems to capture the conductivity effects of Alfvénic Poynting flux-driven broadband electron precipitation in the premidnight and in regions flanking the noon local time (LT) sectors [Keiling et al, 2003;Chaston et al, 2007;Zhang et al, 2014]. The first mode captures variability associated with diffuse precipitation [Newell et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al () have recently studied the influence of IMF clock angle ϕsmallIMF=tan1(By/Bz) on nightside and dayside generation of Alfvénic power using the Lyon‐Fedder‐Mobarry (LFM) global MHD model coupled with the MIX Magnetosphere‐Ionosphere Solver (Merkin & Lyon, ). In their study, Alfvénic Poynting flux is primarily defined on the basis of Polar spacecraft observations at 4–6 R E of large‐amplitude Alfvén waves within a frequency band between approximately 2 and 20 mHz, which overlaps with Pc4–Pc5 bands.…”
Section: Introductionmentioning
confidence: 99%
“…This predicted dependence of the “Alfvénic cusp” is opposite the observed dependence of direct‐entry precipitation, which moves prenoon under dawnward IMF and postnoon under duskward IMF (e.g., Zhou et al, ). Furthermore, Zhang et al () report that the linear relationship between southward IMF magnitude and hemispheric integrated Alfvénic power becomes nonlinear when IMF B y is large, which could suggest that Alfvénic power driven by IMF B z may be produced by a different mechanism than the Alfvénic power driven by IMF B y .…”
Section: Introductionmentioning
confidence: 99%